(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
Stakeholders at the educational sector have long been interested in finding the optimum method for teaching English as a foreign language (TEFL). The approach to teaching that seems to be the most modern is Communicative Language Teaching (CLT). TBLT, which is regarded as a subset of CLT, was adopted in a new book series called "English for Iraq" The space for learners to interact with language both within and outside of the classroom is supposed to be expanded by TBLT. The current study seeks to elicit and rate the task type included in (English for Iraq) student book. The researchers draw upon Nunan (1999) taxonomy of task types. Book number (3) was chosen by researchers. The student book was reviewed, tasks were extracted, classified and analysed. Findings revealed that linguistic and cognitive tasks were more frequently used. Interpersonal, and affective tasks were the least common pedagogical tasks presented in English for Iraq book. The current study findings are helpful for English language teachers aiding them in their career by expanding their awareness of the task types utilized in English for Iraq student books which leads to a better performance of their lessons and better selection for class activities and participants who are proper for the task purposes. Moreover, the findings could be helpful for English for Iraq material developers to work on adding more kinds of tasks and enrich the student books with more communicative tasks.